Patient safety awareness, knowledge and attitude about fire risk assessment during time‐out among perioperative nurses in Korea - Ok‐Hee Cho; Dayun Lee; Kyung‐Hye Hwang (Wiley, 2022)
Abstract Aim This study aims to investigate the relationship between patient safety awareness, knowledge (risk‐Knowledge) and attitude about fire risk assessment during time‐out (risk‐Attitude) of perioperative nurses. Design A cross‐sectional study. Methods Perioperative nurses (N = 158) from 22 small‐ and medium‐sized hospitals participated in the study. Participants' characteristics, knowledge and attitude about fire risk assessment were investigated using structured questionnaires. Results Patient safety awareness, risk‐Knowledge and risk‐Attitude scores were high among nurses who received frequent patient safety education or fire preparedness training, while patient safety awareness partially mediated the effect of risk‐Knowledge on risk‐Attitude. To increase perioperative nurses' risk‐Attitude, it would be effective to increase not only their risk‐Knowledge but also overall patient safety awareness.